Systematic Development of Sertraline Loaded Solid Lipid Nanoparticle (SLN) by Emulsification-Ultrasonication Method and Pharmacokinetic Study in Sprague-Dawley Rats - Rahman, Mohammad A.; Harwansh, Ranjit K.; Iqbal, Zeenat (Pharmaceutical Nanotechnology, 2019)
Objective: To circumvent the aforementioned problems and for the successful delivery of those newly discovered poorly soluble compounds, researchers have focused on the feasibility of biocompatible lipids such as Solid lipid nanoparticles (SLN) as carrier system. Background: Sertraline (SRT) is commercially available as hydrochloride salt. Poor bioavailability (around 44%) of hydrochloride salt is considered to be conversion of salts to free base in the gastrointestinal tract which retard it’s absorption. Methods: Different batches of solid lipid nanoparticles (SLN) were prepared and on the basis of particle size, polydispersity index (PDI), zeta potential (ZP), encapsulation efficiency (EE), and drug loading capacity (L) an optimum system was designed. Results: The optimized formulation contains; 5% (w/v) Compritol® E ATO as lipids, 2.5% (w/v) Tween® 80 as surfactant and 0.1% (w/v) SRT as actives. The formulation was freeze-dried using mannitol as a cryoprotectant to control the aggregation of particles during redispersion process. SLN with <110 nm size, <0.2 PDI, >36 mV ZP, >72% EE, and nearly 0.7% L can be formed at appropriate formulation process conditions; homogenization time (HT) and sonication time (ST) at 5 min and 10 min, respectively. XRD studies indicated the presence of amorphous form of drug that is completely encapsulated within the nanoparticulate matrix system. The optimized SLN formulation have shown the highest value of zeta potential (-36.5 mV) confers stability of nanodispersion. Release of drug encapsulated in SLN showed a biphasic pattern and was extended upto 12 hours. The maximum plasma concentration (Cmax) and area under the curve (AUC) in case of sertraline loaded SLN were found 10-fold and 6-fold higher, respectively compared to pure drug. Conclusion: The result depicted enhanced extent of absorption of sertraline from SLN compared to plain sertraline. Furthermore, sertraline-loaded SLN were found to be stable at 4°C for 6 months of study period. Hence, the SLN can be used as a potential carrier for successful delivery of poorly water-soluble drugs associated with poor oral bioavailability like sertraline.
Keywords: drug release